Total Bakteri Asam Laktat (BAL), Uji pH, dan Sensorik Pada Ileum Ayam Broiler yang Diberi Ransum Bersinbiotik: Total Lactic Acid Bacteria (LAB), pH Test, and Sensory Tests in the Ileum of Broiler Chickens Given Synbiotic Rations - Najib, Muhammad Sufyan; Rinawidiastuti, Rinawidiastuti; Mudawaroch, Roisu Eny (Jurnal Riset Agribisnis dan Peternakan, 2025)
This study aims to examine the effect of different concentrations of synbiotic flour derived from a mixture of jicama inulin, pineapple peel, molasses, and EM-4 as a feed supplement in the ration on the total lactic acid bacteria (LAB), pH, and sensory characteristics of the ileum in broiler chickens. The research employed a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments consisted of synbiotic flour supplementation (P), with P0 = 0%, P1 = 5%, P2 = 10%, P3 = 15%, and P4 = 20%. The observed parameters included total lactic acid bacteria (LAB), pH, and sensory attributes (color, texture, and odor). Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test at a 5% significance level. The results showed that the addition of different concentrations of synbiotic flour had a significant effect (P<0.05) on the total lactic acid bacteria in the ileum of broiler chickens, with mean values of P0: 8.29; P1: 8.30; P2: 9.47; P3: 9.94; and P4: 10.01 log cfu/g. The synbiotic flour concentration also significantly affected (P<0.05) the ileum pH, with mean values of P0: 5.94; P1: 5.67; P2: 5.30; P3: 5.16; and P4: 4.80. Furthermore, synbiotic flour significantly influenced (P<0.05) the color score of the ileum with mean scores of P0: 4.57; P1: 2.17; P2: 3.00; P3: 4.63; and P4: 4.30, the texture score with P0: 4.70; P1: 3.10; P2: 3.70; P3: 4.20; and P4: 4.70, and the odor score with P0: 2.23; P1: 2.90; P2: 3.07; P3: 3.97; and P4: 4.70. In conclusion, the addition of synbiotic flour significantly affects the total lactic acid bacteria (LAB), pH, and sensory characteristics of the ileum in broiler chickens.